Dispersion strengthened copper powder, dispersion strengthened copper part and red and blue composite laser additive manufacturing method of dispersion strengthened copper powder and dispersion strengthened copper part

By preparing dispersively strengthened copper powder and combining red and blue composite laser direct molding technology, the tensile stress problem caused by temperature difference in additive manufacturing is solved, and the mechanical properties and molding quality of the parts are improved.

CN119216588AActive Publication Date: 2024-12-31JIANGXI COPPER TECHNOLOGY RESEARCH INSTITUTE CO LTD

Patent Information

Application Number
CN202411307097.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-31
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

During the additive manufacturing process, diffusion reinforced copper causes large tensile stresses to occur inside the parts due to large temperature differences, resulting in insufficient mechanical properties and deformation and cracking.

Method used

A preparation method is used to prepare diffusely enhanced copper powder, including pre-smelting of Cu, Ni and Al alloys, and adding Sn and Si through high-energy ball mills, performing internal oxidation and reduction reactions to achieve inter-element atomic alloying, and simultaneously use The red-blue composite laser direct molding additive manufacturing device uses blue laser to assist beam preheating and infrared laser melting to improve the density and mechanical properties of the parts.

Benefits of technology

Through the atomic horizontal alloying between elements and the thermal effect of red and blue composite laser, the density, conductivity and mechanical quality of the parts are improved, the internal stress and temperature gradient are reduced, deformation and cracking are avoided, and the metal forming quality is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119216588A_ABST
    Figure CN119216588A_ABST
Patent Text Reader

Abstract

The invention discloses dispersion strengthened copper powder, a dispersion strengthened copper part and a red and blue composite laser additive manufacturing method of the dispersion strengthened copper part, and relates to the field of laser additive manufacturing. The dispersion strengthened copper powder comprises Ni, Al, Sn, Si and the balance of copper; the additive manufacturing method comprises the steps that a part CAD model is drawn, the red and blue composite laser direct forming additive manufacturing device is adopted for conducting additive manufacturing on dispersion strengthened copper powder, the laser power is adjusted, and the dispersion strengthened copper part is obtained. According to the method, Cu-Ni-Al alloy powder, Sn and Si powder are subjected to mechanical alloying through high-energy ball milling, segregation of Si and Sn in the alloy smelting process is avoided, the low reflection effect of copper alloy on blue laser and the heat effect of infrared laser are utilized in the additive manufacturing process, the laser energy utilization rate is increased, and the production cost is reduced. And meanwhile, the blue laser auxiliary beam is preheated before the red-blue composite beam passes through, the temperature gradient on the surface of the part is reduced, residual stress is reduced, and the forming quality of the part is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of laser additive manufacturing, and in particular to a dispersion-strengthened copper powder and a dispersion-strengthened copper part and a red-blue composite laser additive manufacturing method thereof. Background Art

[0002] Laser Metal Deposition (LMD) uses a high-energy laser beam as a heat source, and the laser energy density is high. This technology can quickly reach the melting point of the processed metal, realize rapid melting, solidification, and forming processes, thereby achieving the effect of metallurgical bonding, and has the characteristics of high energy utilization, high processing flexibility, high part forming efficiency, and high part forming quality. This technology can perform fine processing and manufacturing of complex three-dimensional high-precision parts, and is widely used in direct part processing and manufacturing, high-performance component cladding, part repair and other fields.

[0003] The absorption rate of metal materials to lasers directly affects the quality and performance of molded parts. Copper and copper alloys have high reflectivity to infrared lasers. The reflectivity of pure copper under 1064nm infrared laser irradiation is as high as 95.2%. At the same time, copper's reflection of lasers will also affect the service life of the laser. Due to the high reflectivity of copper, it is difficult to completely melt the processed powder under infrared laser irradiation during laser additive manufacturing, and it is easy to produce defects such as holes and cracks, thereby affecting the density of processed parts. The absorption rate of copper and copper alloys to short-wavelength blue lasers (450nm) has increased by more than 10 times, greatly reducing the loss of laser power. However, since blue lasers are relatively expensive and short-wavelength blue lasers do not have the photothermal effect of infrared lasers, further development is limited.

[0004] Copper-nickel-tin alloy has excellent electrical and thermal conductivity and is widely used in the electronics industry, shipbuilding, automobiles and other fields. However, with the development of microelectronics and industrial automation, higher requirements are placed on copper-nickel-tin alloy. Oxide dispersion-strengthened copper has excellent high-temperature mechanical properties, radiation resistance, high-temperature softening resistance and high-temperature creep resistance. The dispersed nano-second phase oxide plays a role in pinning dislocations, preventing dislocation movement and grain boundary sliding, and further improving the mechanical properties of copper alloys. However, in the additive manufacturing process of dispersion-strengthened copper powder, the periodically moving molten pool will experience rapid heating and rapid cooling. When the non-equilibrium solid phase phase transition occurs during solidification and shrinkage at the bottom of the molten pool, large tensile stress will be generated inside the part, resulting in insufficient mechanical properties of the part and easy deformation and cracking. Summary of the invention

[0005] The present invention provides a dispersion-strengthened copper powder and a dispersion-strengthened copper part and a laser additive manufacturing method thereof, so as to solve the technical problem that during the additive manufacturing process of dispersion-strengthened copper, a large temperature difference causes large tensile stress inside the part, resulting in insufficient mechanical properties and deformation and cracking of the part.

[0006] In order to solve the above technical problems, one of the purposes of the present invention is to provide a method for preparing a dispersion-strengthened copper powder, wherein the dispersion-strengthened copper powder comprises 10wt%-15wt% Ni, 0.2wt%-0.7wt% Al, 5wt%-10wt% Sn, 0.1wt%-5wt% Si, and the remainder is copper and unavoidable impurities, and the preparation method comprises the following steps:

[0007] (1) preparing powders of pure Cu, pure Ni and pure Al by gas atomization according to the alloy composition, and sieving to obtain Cu-Ni-Al alloy powder;

[0008] (2) mixing the Cu-Ni-Al alloy powder with the pure Sn powder and the pure Si powder, and performing high-energy ball milling alloying under the protection of an inert gas, first setting the speed of the first high-energy ball milling to 200-400 r / min and the ball milling time to 0.5-2 h, and then setting the speed of the second high-energy ball milling to 800-1200 r / min and the ball milling time to 5-10 h, to obtain a mechanically alloyed powder;

[0009] (3) After the mechanical alloying powder and Cu2O powder are fully mixed, an internal oxidation reaction is carried out in an inert gas atmosphere, the reaction temperature is 750-950°C, the reaction time is 1-5h, the atomic ratio of Al in the mechanical alloying powder to O in the Cu2O powder is 1:(1.5-2), and the powders are mixed by high-energy ball milling to obtain a mixed powder;

[0010] (4) subjecting the mixed powder to a reduction reaction in a reducing gas atmosphere at a reaction temperature of 400-700° C. for a reaction time of 3-10 h to obtain a dispersion-strengthened copper powder.

[0011] By adopting the above scheme, the dispersion-strengthened copper powder prepared in the present application is evenly dispersed, Si can reduce red light reflection and improve laser absorptivity. Since Si and Sn have large density differences with Cu and low solid solubility in Cu, Si and Sn are prone to segregation during alloy smelting, resulting in uneven component dispersion. Therefore, the present invention pre-smelts Cu, Ni and Al evenly, and then adds Sn and Si by high-energy ball milling, so that the Cu-Ni-Al alloy powder and Sn powder, Si powder are subjected to repeated deformation, cold welding, and crushing, so that each element reaches or approaches the atomic-level distance at the contact points, lines and surfaces within a limited ball milling time, thereby achieving atomic-level alloying between elements, which is beneficial to improving the density, conductivity and mechanical quality of parts when used in subsequent additive manufacturing processes.

[0012] As a preferred solution, in step (1), the melting times are 3-6 times, and the vacuum degree of the melting furnace is 0.1 -2 Pa, the melting temperature is 1500℃-2000℃.

[0013] As a preferred embodiment, in step (1), pure Cu is a powder with a particle size of 50-100 μm; pure Ni is a powder with a particle size of 30-50 μm; and pure Al is a powder with a particle size of 30-50 μm.

[0014] As a preferred embodiment, in step (1), the particle size of the sieved Cu-Ni-Al alloy powder is 300-500 mesh.

[0015] As a preferred embodiment, in step (2), the grinding balls and ball milling jars for the first high-energy ball milling are made of agate, the grinding balls have a diameter of 4 mm, and the ball-to-material mass ratio is (10-15):1. The grinding balls for the second high-energy ball milling are mixed grinding balls of 4 mm diameter and 2 mm diameter in a mass ratio of 1:1, and the ball-to-material ratio is (4-10):1.

[0016] As a preferred embodiment, in step (2), the rotation direction of the high energy ball mill is set to alternately rotate clockwise and counterclockwise with an interval of 0.5 h.

[0017] As a preferred embodiment, in step (3), the particle size of the Cu2O powder is 30-50 μm.

[0018] As a preferred embodiment, in step (3), the rotation speed of the high-energy ball mill is 100-300 r / min, the ball milling time is 0.5-1 h, the grinding ball diameter is 4 mm, and the ball-to-material mass ratio is (10-15):1.

[0019] As a preferred solution, in step (4), the reducing gas is argon and hydrogen, and the flow rate of argon is set to 50-100 Sccm, and the flow rate of hydrogen is set to 50-100 Sccm.

[0020] In order to solve the above technical problems, a second object of the present invention is to provide a dispersion strengthened copper powder.

[0021] In order to solve the above technical problems, the third object of the present invention provides a red-blue composite laser direct forming additive manufacturing device, including a blue laser transmitter, an infrared laser transmitter, a red-blue composite laser focusing lens, a blue light focusing lens, a red-blue composite laser fast axis collimator, a blue laser fast axis collimator, a coaxial powder feeder and a substrate, wherein the powder in the coaxial powder feeder is a dispersion-strengthened copper powder;

[0022] The blue light emitted by the blue laser emitter is respectively reflected to the red-blue composite laser focusing perspective mirror and the blue light focusing lens, and the infrared light emitted by the infrared laser emitter is reflected to the red-blue composite laser focusing perspective mirror. The red-blue composite laser focusing perspective mirror coaxially combines the passing blue light and infrared light to form a red-blue composite light beam with a blue laser main beam on the outside and an infrared laser beam on the inside. The red-blue composite light beam passes through a red-blue composite laser fast axis collimator and forms a coaxial light spot of an outer blue light main spot and an inner infrared light spot on the substrate through a nozzle, which is used for additive manufacturing in a second molding area on the substrate;

[0023] The blue light passes through a blue light focusing lens to form a blue light laser auxiliary beam. The blue light laser auxiliary beam passes through a blue light laser fast axis collimator and forms a blue light auxiliary spot on the substrate, which is used for laser preheating in the first molding area on the substrate. The moving trajectory of the red and blue composite beam is the same as the moving trajectory of the blue light laser auxiliary beam on the substrate. The first molding area is located in front of the moving direction of the second molding area, and the first molding area and the second molding area are molded at the same time.

[0024] By adopting the above scheme, the blue light and infrared light emitted by the blue laser transmitter and the infrared laser transmitter are coaxially combined at the red-blue composite laser focusing perspective mirror to form a red-blue composite beam, the outer side of the red-blue composite beam is a blue beam, and the inner side is an infrared beam. The high absorption rate of copper or copper alloy to the blue laser causes the copper to melt quickly and form a hole key. The infrared laser is reflected multiple times in the formed hole key, so that its absorption rate is improved. The low reflection effect of copper alloy on the blue laser and the thermal effect of the infrared laser are used to improve the utilization rate of laser energy. Under the irradiation of the red-blue composite laser, the stability of the molten pool will be significantly improved and the range of the heat-affected zone will be significantly reduced. The temperature gradient of the part surface is reduced, the generation of internal stress is reduced, and the quality of metal forming is improved. At the same time, the blue laser auxiliary beam is used to preheat the substrate in advance, which can reduce the temperature gradient and avoid deformation and cracking of metal forming products due to rapid cooling and heating.

[0025] As a preferred solution, the blue light emitted by the blue laser emitter is reflected by the blue laser reflector to the red-blue composite laser focusing perspective mirror, the infrared light emitted by the infrared laser emitter is reflected by the infrared laser reflector to the red-blue composite laser focusing perspective mirror, and the blue light emitted by the blue laser emitter is reflected by the blue light excitation part reflector to the blue light focusing lens.

[0026] As a preferred solution, the red-blue composite light beam and the blue laser auxiliary light beam are parallel to each other.

[0027] As a preferred solution, the coaxial powder feeder delivers the dispersion-strengthened copper powder to the red-blue composite light beam path at the nozzle location, so that the dispersion-strengthened copper powder and the red-blue composite light beam intersect at one point.

[0028] In order to solve the above technical problems, the fourth object of the present invention provides a red-blue composite laser additive manufacturing method for dispersion-strengthened copper parts, using the dispersion-strengthened copper powder and the red-blue composite laser direct forming additive manufacturing device, comprising the following steps:

[0029] A CAD model is drawn according to the three-dimensional size of the processed part, and a red-blue composite laser direct forming additive manufacturing device is used to perform an additive manufacturing process on the dispersion-strengthened copper powder. The parameters of the red-blue composite laser direct forming additive manufacturing device are adjusted, and the laser power of the infrared laser beam varies in the range of 1000-3000W, the laser power of the blue laser main beam varies in the range of 1500-4000W, and the laser power of the blue laser auxiliary beam varies in the range of 200-1000W to obtain a dispersion-strengthened copper part.

[0030] By adopting the above scheme, during the additive manufacturing process, the periodically moving molten pool will experience rapid heating and rapid cooling. When the non-equilibrium solid phase phase change occurs at the bottom of the molten pool due to solidification and shrinkage, a large tensile stress will be generated inside the part, causing the part to deform and crack. The present application uses a blue laser auxiliary beam to preheat the part before the red and blue composite beam passes through, so as to avoid the rapid cooling and solidification of the material at the bottom of the molten pool and then undergo a rapid heating stage, thereby reducing the temperature gradient on the surface of the part and reducing the generation of residual stress, thereby improving the molding quality of the part.

[0031] As a preferred solution, the parameters of the red-blue composite laser direct forming additive manufacturing device are adjusted to control the radius of the infrared spot to R1, the range of R1 is 0.01-2mm, the radius of the blue light main spot is R2, the range of R2 is 0.01-2mm, the radius of the blue light auxiliary spot is R3, the range of R3 is 0.01-2.5mm, and R1≤R2.

[0032] By adopting the above scheme, the present application sets the processing parameters of the first molding area and the second molding area and adjusts the spot radius according to the three-dimensional size of the part. The two areas are relatively independent and molded simultaneously. The simultaneous additive manufacturing of three light beams can reduce the temperature gradient on the surface of the part and reduce the generation of residual stress, thereby improving the molding quality of the part.

[0033] In order to solve the above technical problems, a fifth object of the present invention is to provide a dispersion strengthened copper part.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. In the present application, Cu, Ni and Al are alloyed uniformly in advance, and then Sn and Si are added by high-energy ball milling to achieve alloying at the atomic level between the elements, thereby avoiding the segregation of Si and Sn during the alloy melting process, which leads to uneven dispersion of the components, and is beneficial to improving the density, conductivity and mechanical quality of the parts when used in the subsequent additive manufacturing process.

[0036] 2. The blue light and infrared light emitted by the blue laser transmitter and the infrared laser transmitter are coaxially combined at the red-blue composite laser focusing perspective mirror to form a red-blue composite light beam. The low reflection effect of copper alloy on the blue laser and the thermal effect of the infrared laser are used to improve the utilization rate of the laser energy. Under the irradiation of the red-blue composite laser, the stability of the molten pool will be significantly improved and the range of the heat-affected zone will be significantly reduced. The temperature gradient on the surface of the part is reduced, the generation of internal stress is reduced, and the metal forming quality is improved.

[0037] 3. In the additive manufacturing process, the periodically moving molten pool will experience rapid heating and rapid cooling. When the non-equilibrium solid phase phase change occurs at the bottom of the molten pool due to solidification and shrinkage, a large tensile stress will be generated inside the part, causing the part to deform and crack. This application uses a blue laser auxiliary beam to preheat the part before the red and blue composite beam passes through, avoiding the rapid cooling and solidification of the material at the bottom of the molten pool and then undergoing a rapid heating stage, thereby reducing the temperature gradient on the surface of the part and reducing the generation of residual stress, thereby improving the molding quality of the part. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 : is a structural schematic diagram of a red-blue composite laser additive manufacturing device in Example 2 of the present invention;

[0039] Figure 2 : A scanning electron microscope image of a mechanically alloyed powder obtained in step (3) of the method for preparing a dispersion-strengthened copper powder in Example 1 of the present invention;

[0040] Figure 3 : A scanning electron microscope image of the internal distribution of a dispersion-strengthened copper part sample in Example 3 of the present invention;

[0041] Figure 4 :for Figure 3 Scanning electron microscopy (EDS) analysis of area A of the sample.

[0042] The instruction manual is attached Figure 1The figure markings are as follows: 1. blue laser transmitter; 2. infrared laser transmitter; 3. blue laser partial reflector; 4. blue laser reflector; 5. infrared laser reflector; 6. red-blue composite laser focusing lens; 7. blue light focusing lens; 8. red-blue composite laser fast axis collimator; 9. blue laser fast axis collimator; 10. infrared laser beam; 11. blue laser auxiliary beam; 12. blue laser main beam; 13. coaxial powder feeder; 14. substrate; 15. first molding area; 16. second molding area; 17. blue light main spot; 18. infrared spot; 19. blue light auxiliary spot. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Embodiment 1

[0045] A method for preparing a dispersion-strengthened copper powder, the dispersion-strengthened copper powder comprising 15wt% Ni, 0.6wt% Al, 10wt% Sn, 2wt% Si and the remainder copper, the preparation method comprising the following steps:

[0046] (1) High-purity Cu powder, high-purity Ni powder, and high-purity Al powder with a purity of 99.9 wt% were repeatedly smelted in a vacuum melting furnace for 4 times to ensure that the alloy composition was uniform. The vacuum degree of the melting furnace was controlled at 0.1 -2 Pa, the temperature of the smelting furnace is controlled at 2000°C, the particle size of the high-purity Cu powder is 50μm, the particle size of the high-purity Ni powder is 30μm, and the particle size of the high-purity Al powder is 30μm;

[0047] (2) preparing Cu-Ni-Al alloy powder by gas atomization, using high-purity nitrogen as the protective gas during the powder preparation process, sieving the alloy powder with a particle size of 300 mesh through a standard molecular sieve, and selecting the powder with spherical particle shape, uniform particle size distribution, smooth particle surface, and a small amount of satellite spheres as the Cu-Ni-Al alloy powder to be used;

[0048] (3) The Cu-Ni-Al alloy powder is mixed with high-purity Sn powder and high-purity Si powder with a purity of 99.9wt%, and high-energy ball milling alloying is performed under inert gas protection. The particle size of the high-purity Sn powder is 30μm, and the particle size of the high-purity Si powder is 30μm. First, the mixed powder is ball milled, and the speed of the high-energy ball mill is set to 400r / min, the ball milling time is 1h, the material of the grinding ball and the ball mill is agate, the grinding ball diameter is 4mm, and the ball-to-material mass ratio is 10:1. Then, mechanical alloying ball milling is performed, and the speed of the high-energy ball mill is set to 1000r / min, the ball milling time is 8h, the grinding balls are mixed grinding balls with a mass ratio of 1:1, with a diameter of 4mm and a diameter of 2mm, and the ball-to-material mass ratio is 10:1. To ensure that the mechanical alloying is fully carried out, the rotation direction of the ball mill is set to alternately clockwise and counterclockwise, with an interval time of 0.5h, to obtain mechanical alloying powder;

[0049] (4) The mechanical alloying powder and Cu2O powder were ball-milled and mixed, the atomic ratio of Al content in the mechanical alloying powder to O content in the Cu2O powder was 1:15, the particle size of the Cu2O powder was 30 μm, and the powders were mixed by high-energy ball milling. The speed of the high-energy ball mill was set to 200 r / min, the ball milling time was 1 h, the grinding ball diameter was 4 mm, and the ball-to-material mass ratio was 10:1. Subsequently, the mixed powder was subjected to internal oxidation reaction under the protection of inert gas argon, the reaction temperature was 850 ° C, and the reaction time was 3 h;

[0050] (5) The mixed powder obtained in step (4) is subjected to a reduction reaction in an atmosphere of a mixed gas of argon and hydrogen, with the flow rate of argon set to 50 sccm, the flow rate of hydrogen set to 50 sccm, the reaction temperature set to 450° C., and the reaction time set to 5 h, to obtain a dispersion-strengthened copper powder.

[0051] In step (3), the present application uses high-energy ball milling to subject the Cu-Ni-Al alloy powder, Sn powder, and Si powder to repeated deformation, cold welding, and crushing, so that the elements can reach or approach the atomic level distance at the contact points, lines, and surfaces within a limited ball milling time, thereby achieving atomic-level alloying between the elements, such as Figure 1 As shown, the mechanical alloying powder obtained after high-energy ball milling in step (3) has uniformly dispersed components.

[0052] Example 2

[0053] A red-blue composite laser direct forming additive manufacturing device, such as Figure 2 As shown, it includes a blue light laser transmitter 1, an infrared laser transmitter 2, a blue light laser reflector 4, an infrared laser reflector 5, a red-blue composite laser focusing lens 6, a blue light focusing lens 7, a red-blue composite laser fast axis collimator 8, a blue light laser fast axis collimator 9 and a coaxial powder feeder 13.

[0054] Specifically, the blue light path emitted by the blue laser emitter 1 and the infrared light path emitted by the infrared laser emitter 2 are parallel to each other, the blue laser reflector 4 is located at one end of the blue light path away from the blue laser emitter 1, and the blue laser reflector 4 reflects the passing blue light beam at right angles to the red-blue composite laser focusing perspective mirror 6; the infrared laser reflector 5 is located at one end of the infrared light path away from the infrared laser emitter 2, and the infrared laser reflector 5 reflects the passing infrared light beam at right angles to the red-blue composite laser focusing perspective mirror 6. The red-blue composite laser focusing perspective mirror 6 coaxially combines the passing blue light beam and the infrared light beam to form a red-blue composite light beam with a blue laser main beam 12 on the outside and an infrared laser beam 10 on the inside. The red-blue composite laser fast axis collimator 8 is located on one side of the red-blue composite laser focusing perspective mirror 6, and the red-blue composite light beam vertically passes through the red-blue composite laser fast axis collimator 8, and forms a coaxial outer blue light main spot 17 and an inner infrared light spot 18 on the substrate 14 through the nozzle, so as to realize additive manufacturing in the second molding area 16 on the substrate.

[0055] In view of the large diameter of the blue laser spot, low maximum output power, and high cost, the present application uses a red-blue composite laser to realize the additive manufacturing or cladding manufacturing of copper and copper alloy high-reflective materials. Copper's high absorption rate of blue laser causes copper to melt quickly and form a keyhole. The infrared laser undergoes multiple reflections in the formed keyhole, which increases its absorption rate. Therefore, under the irradiation of the red-blue composite laser, the stability of the molten pool will be significantly improved and the range of the heat-affected zone will be significantly reduced. The reduction of the surface temperature gradient of the part reduces the generation of internal stress, and the metal forming quality is significantly better than that of a single heat source. The coaxial powder feeder 13 delivers the copper alloy powder to the red-blue composite beam path at the nozzle position, so that the copper alloy powder intersects with the red-blue composite beam at one point, and the copper alloy powder is melted by laser irradiation and quickly solidified into shape.

[0056] Specifically, a blue light excitation partial reflector 3 is also arranged between the blue light laser emitter 1 and the blue light excitation reflector 4 located in the blue light path. The blue light excitation partial reflector 3 reflects part of the passing blue light at a right angle to the blue light focusing lens 7. The blue light passes through the blue light focusing lens 7 to form a blue light laser auxiliary beam 11. The blue light laser fast axis collimator 9 is located on one side of the blue light focusing lens 7. The blue light laser auxiliary beam 11 passes through the blue light laser fast axis collimator 9 vertically and forms a blue light auxiliary spot 19 on the substrate 14 to realize laser preheating in the first molding area 15 on the substrate 14.

[0057] The first molding area 15 is located in front of the moving forward direction of the second molding area 16, and the moving trajectory of the red-blue composite light beam is the same as the moving trajectory of the blue laser auxiliary light beam 11 on the substrate 14, and the first molding area 15 and the second molding area 16 are molded at the same time. The blue laser auxiliary light beam 11 can perform blue light preheating on the first molding area 15 on the substrate 14, and then wait for the red-blue composite light beam to move to the first molding area 15 for laser cladding. In the additive manufacturing process, since the periodically moving molten pool will undergo rapid heating and rapid cooling, when the non-equilibrium solid phase phase transition occurs at the bottom of the molten pool due to solidification and shrinkage, a large tensile stress will be generated inside the part, causing deformation and cracking of the part. The substrate of the present application uses a blue laser auxiliary light beam 11 to preheat before the red-blue composite light beam passes, so as to avoid the rapid cooling and solidification of the material at the bottom of the molten pool and then undergo a rapid heating stage, reduce the temperature gradient on the surface of the part, and reduce the generation of residual stress, thereby improving the molding quality of the part.

[0058] Example 3

[0059] A red-blue composite laser additive manufacturing method for dispersion-strengthened copper parts, using the red-blue composite laser direct forming additive manufacturing device of Example 2, comprises the following steps:

[0060] (1) adjusting the angles of the infrared laser reflector 5 and the blue laser reflector 4 and the positions of the red-blue composite laser focusing lens 6 and the red-blue composite laser fast axis collimator 8 so that the infrared laser beam 10 and the blue laser main beam 12 form a red-blue composite beam, and the infrared light spot 18 formed is concentric with the blue light main spot 17. By adjusting the angle of the blue laser partial reflector 3 and the positions of the blue light focusing lens 7 and the blue laser fast axis collimator 9, the blue laser auxiliary beam 11 is parallel to the red-blue composite beam, and the outer diameter distance d between the blue auxiliary light spot 19 and the red-blue composite beam is 0.1 mm.

[0061] (2) The radius of the infrared light spot 18 is set to R1 = 0.3 mm, the radius of the blue light main light spot 17 is set to R2 = 0.4 mm, and the radius of the blue light auxiliary light spot 19 is set to R3 = 0.6 mm;

[0062] (3) setting the laser power of the infrared laser beam 10 to 2000 W, the laser power of the blue laser main beam 12 to 3000 W, and the laser power of the blue laser auxiliary beam 11 to 1000 W;

[0063] (4) A CAD model was drawn according to the three-dimensional dimensions of the machined parts, and the dispersion-strengthened copper powder obtained in Example 1 was subjected to an additive manufacturing process using a red-blue composite laser coaxially coupled powder feeding laser direct forming technology. The scanning rates of the blue laser beam and the infrared laser beam were both set to 0.8 m / min, the powder blowing gas flow rate of the powder feeder was 8 L / min, and the scanning length was 80 mm, thereby obtaining a high-precision, high-density dispersion-strengthened copper part.

[0064] like Figure 3 As shown in the figure, the internal distribution scanning results of the dispersion-strengthened copper parts prepared in Example 3 show that there is a high-density dispersion-strengthened phase inside the sample, and the distribution is uniform, and the size of the dispersed phase is concentrated in 12-17nm. Figure 4 As shown, the scanning result area A of the dispersion strengthened copper part in Example 3 is detected, and the main component of the obtained dispersion strengthened phase is Al2O3.

[0065] Comparative Example 1

[0066] A method for preparing a dispersion-strengthened copper powder, the dispersion-strengthened copper powder comprising 15wt% Ni, 0.6wt% Al, 10wt% Sn, 2wt% Si and the remainder copper, the preparation method comprising the following steps:

[0067] (1) High-purity Cu powder, high-purity Ni powder, high-purity Al powder, high-purity Sn powder, and high-purity Si powder with a purity of 99.9 wt% were repeatedly smelted in a vacuum melting furnace for 4 times to ensure that the alloy composition was uniform. The vacuum degree of the melting furnace was controlled at 0.1 -2 Pa, the temperature of the smelting furnace is controlled at 2000°C, the particle size of the high-purity Cu powder is 50μm, the particle size of the high-purity Ni powder is 30μm, the particle size of the high-purity Al powder is 30μm, the particle size of the high-purity Sn powder is 30μm, and the particle size of the high-purity Si powder is 30μm;

[0068] (2) preparing alloy powder by gas atomization, using high-purity nitrogen as protective gas during the powder making process, sieving alloy powder with a particle size of 300 mesh through a standard molecular sieve, and selecting powder with spherical particle shape, uniform particle size distribution, smooth particle surface, and a small amount of satellite spheres as the alloy powder to be used;

[0069] (3) The alloy powder and Cu2O powder were ball-milled and mixed, the atomic ratio of Al content in the alloy powder to O content in the Cu2O powder was 1:15, the particle size of the Cu2O powder was 30 μm, and the powders were mixed by high-energy ball milling. The speed of the high-energy ball mill was set to 200 r / min, the ball milling time was 1 h, the grinding ball diameter was 4 mm, and the ball-to-material mass ratio was 10:1. Subsequently, the mixed powder was subjected to internal oxidation reaction under the protection of inert gas argon, the reaction temperature was 850 ° C, and the reaction time was 3 h;

[0070] (4) The mixed powder obtained in step (3) is subjected to a reduction reaction in an atmosphere of a mixed gas of argon and hydrogen, with the flow rate of argon set to 50 sccm, the flow rate of hydrogen set to 50 sccm, the reaction temperature set to 450° C., and the reaction time set to 5 h, to obtain a dispersion-strengthened copper powder.

[0071] Comparative Example 2

[0072] A red-blue composite laser additive manufacturing method for dispersion-strengthened copper parts, wherein each step and the equipment, reagents, and process parameters used in each step are the same as those in Example 3, except that, in step (4), the dispersion-strengthened copper prepared in Comparative Example 1 is used instead of the dispersion-strengthened copper prepared in Example 1.

[0073] The dispersion-strengthened copper parts prepared in Example 3 and Comparative Example 2 were tested for density, Vickers hardness, and compressive strength. It was found that the performance of the product in Comparative Example 2 was inferior to that of the product in Example 3.

[0074] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing dispersion-strengthened copper powder, characterized in that: The dispersion-strengthened copper powder comprises 10wt%-15wt% Ni, 0.2wt%-0.7wt% Al, 5wt%-10wt% Sn, 0.1wt%-5wt% Si, and the remainder is copper and unavoidable impurities. The preparation method comprises the following steps: (1) After pure Cu, pure Ni and pure Al are mixed and smelted uniformly according to the alloy composition, powder is prepared by gas atomization, and Cu-Ni-Al alloy powder is obtained by sieving; (2) mixing the Cu-Ni-Al alloy powder with the pure Sn powder and the pure Si powder, and performing high-energy ball milling alloying under the protection of an inert gas, first setting the speed of the first high-energy ball milling to 200-400 r / min and the ball milling time to 0.5-2 h, and then setting the speed of the second high-energy ball milling to 800-1200 r / min and the ball milling time to 5-10 h, to obtain a mechanically alloyed powder; (3) After the mechanical alloying powder and Cu2O powder are fully mixed, an internal oxidation reaction is carried out in an inert gas atmosphere, the reaction temperature is 750-950°C, the reaction time is 1-5h, the atomic ratio of Al in the mechanical alloying powder to O in the Cu2O powder is 1:(1.5-2), and the powders are mixed by high-energy ball milling to obtain a mixed powder; (4) subjecting the mixed powder to a reduction reaction in a reducing gas atmosphere at a reaction temperature of 400-700° C. for a reaction time of 3-10 h to obtain a dispersion-strengthened copper powder.

2. The method for preparing a dispersion-strengthened copper powder according to claim 1, characterized in that: Satisfy at least one of the following a)-h): a) In step (1), the melting times are 3-6 times, and the vacuum degree of the melting furnace is 0.1 -2 Pa, melting temperature is 1500℃-2000℃; b) In step (1), pure Cu is a powder with a particle size of 50-100 μm; pure Ni is a powder with a particle size of 30-50 μm; pure Al is a powder with a particle size of 30-50 μm; c) in step (1), the particle size of the sieved Cu-Ni-Al alloy powder is 300-500 mesh; d) In step (2), the grinding balls and the ball milling jar used in the first high-energy ball milling are made of agate, the grinding balls have a diameter of 4 mm, and the ball-to-material mass ratio is (10-15):1; the grinding balls used in the second high-energy ball milling are mixed grinding balls of 4 mm diameter and 2 mm diameter in a mass ratio of 1:1, and the ball-to-material ratio is (4-10):1; e) In step (2), the high energy ball mill is rotated in a clockwise and counterclockwise direction alternately, with an interval of 0.5 h; f) in step (3), the particle size of the Cu2O powder is 30-50 μm; g) In step (3), the rotation speed of the high energy ball mill is 100-300 r / min, the ball milling time is 0.5-1 h, the grinding ball diameter is 4 mm, and the ball-to-material mass ratio is (10-15):1; h) In step (4), the reducing gas is argon and hydrogen, and the flow rate of argon is set to 50-100 Sccm, and the flow rate of hydrogen is set to 50-100 Sccm.

3. A dispersion-strengthened copper powder prepared by the method for preparing dispersion-strengthened copper powder as claimed in claim 1 or 2.

4. A red-blue composite laser direct forming additive manufacturing device, characterized in that: It includes a blue laser transmitter, an infrared laser transmitter, a red-blue composite laser focusing lens, a blue focusing lens, a red-blue composite laser fast axis collimator, a blue laser fast axis collimator, a coaxial powder feeder and a substrate, wherein the powder in the coaxial powder feeder is a dispersion-strengthened copper powder as described in claim 3; The blue light emitted by the blue laser emitter is respectively reflected to the red-blue composite laser focusing perspective mirror and the blue light focusing lens, and the infrared light emitted by the infrared laser emitter is reflected to the red-blue composite laser focusing perspective mirror. The red-blue composite laser focusing perspective mirror coaxially combines the passing blue light and infrared light to form a red-blue composite light beam with a blue laser main beam on the outside and an infrared laser beam on the inside. The red-blue composite light beam passes through a red-blue composite laser fast axis collimator and forms a coaxial light spot of an outer blue light main spot and an inner infrared light spot on the substrate through a nozzle, which is used for additive manufacturing in a second molding area on the substrate; The blue light passes through a blue light focusing lens to form a blue light laser auxiliary beam. The blue light laser auxiliary beam passes through a blue light laser fast axis collimator and forms a blue light auxiliary spot on the substrate, which is used for laser preheating in the first molding area on the substrate. The moving trajectory of the red and blue composite beam is the same as the moving trajectory of the blue light laser auxiliary beam on the substrate. The first molding area is located in front of the moving direction of the second molding area, and the first molding area and the second molding area are molded at the same time.

5. A red-blue composite laser direct structuring additive manufacturing device as claimed in claim 4, characterized in that: The blue light emitted by the blue laser emitter is reflected by the blue laser reflector to the red-blue composite laser focusing perspective mirror, the infrared light emitted by the infrared laser emitter is reflected by the infrared laser reflector to the red-blue composite laser focusing perspective mirror, and the blue light emitted by the blue laser emitter is reflected by the blue light excitation part reflector to the blue light focusing lens.

6. A red-blue composite laser direct structuring additive manufacturing device as claimed in claim 4, characterized in that: The red-blue composite light beam and the blue laser auxiliary light beam are parallel to each other.

7. A red-blue composite laser direct structuring additive manufacturing device as claimed in claim 4, characterized in that: The coaxial powder feeder delivers the dispersion-enhanced copper powder to the red-blue composite light beam path at the nozzle position, so that the dispersion-enhanced copper powder and the red-blue composite light beam intersect at one point.

8. A red-blue composite laser additive manufacturing method for dispersion-strengthened copper parts, characterized in that: Using the dispersion-strengthened copper powder as claimed in claim 3 and the red-blue composite laser direct forming additive manufacturing device as claimed in any one of claims 4 to 7, the following steps are included: A CAD model is drawn according to the three-dimensional size of the processed part, and a red-blue composite laser direct forming additive manufacturing device is used to perform an additive manufacturing process on the dispersion-strengthened copper powder. The parameters of the red-blue composite laser direct forming additive manufacturing device are adjusted, and the laser power of the infrared laser beam varies in the range of 1000-3000W, the laser power of the blue laser main beam varies in the range of 1500-4000W, and the laser power of the blue laser auxiliary beam varies in the range of 200-1000W to obtain a dispersion-strengthened copper part.

9. A red-blue composite laser additive manufacturing method for dispersion-strengthened copper parts as claimed in claim 8, characterized in that: Adjust the parameters of the red-blue composite laser direct forming additive manufacturing device to control the radius of the infrared spot to R1, the range of R1 is 0.01-2mm, the radius of the blue light main spot to R2, the range of R2 is 0.01-2mm, the radius of the blue light auxiliary spot to R3, the range of R3 is 0.01-2.5mm, and R1≤R2.

10. A dispersion-strengthened copper part manufactured by the red-blue composite laser additive manufacturing method for a dispersion-strengthened copper part as claimed in claim 8 or 9.

Citation Information

Patent Citations

  • Dispersed copper composite material and preparation method thereof

    CN105132736A

  • Blue light and infrared dual-wavelength coaxial composite laser additive manufacturing device and method

    CN114012111A

  • Preparation method of wear-resistant aluminum-based composite material

    CN118385605A

  • NANO dispersion copper alloy with high air-tightness and low free oxygen content and brief manufacturing process thereof

    US20210363610A1

Cited By

  • Device for manufacturing magnesium-based composite material through follow-up magnetic field assisted infrared and blue light composite laser additive and application of device

    CN121223118A